Green lubricants in action: a comprehensive performance evaluation of groundnut oil-based cutting fluids in metal machining processes - Srinivas M.S.; Kumar D.; Suvin P.S.; Kailas S.V.; Pawar S.R.; Roy Choudhury M. (My University, 2025)
As industries worldwide seek environmentally sustainable solutions, the metalworking sector faces a growing need for eco-friendly alternatives to traditional cutting fluids. This abstract introduces the concept of an innovative approach to cutting fluid technology—the use of groundnut oil as a base material for machining fluids. Derived from peanuts, groundnut oil presents a renewable and biodegradable alternative to petroleum-based counterparts, addressing concerns related to resource depletion and environmental impact. A comprehensive performance evaluation of groundnut oil- based cutting fluid has been carried out by series of critical tests such as separation testing, particle size and stability testing, frictional testing, corrosion testing and drilling testing. The results of these tests collectively contribute to a comprehensive understanding of groundnut oil-based cutting fluids, shedding light on their potential as sustainable and high-performance alternatives in metalworking. The zeta potential for the prepared green cutting fluid has been found to be 49.10 mV. The dimensions of the dispersed particles in a fluid of the cutting fluid have been found as 250-260 nm. The environmentally friendly cutting fluid exhibits favourable outcomes in corrosion resistance, frictional performance, and drilling efficacy during testing. © 2024 The Author(s). Published by IOP Publishing Ltd.